Оn the selection of an aquifer as an absorbing reservoir for the disposal of industrial wastewater - R.A. Gasumov; E. R. Gasumov (Наука. Инновации. Технологии, 2025)
The article presents the collection, generalization and analysis of geological and field data, as well as the consideration of geological and hydrogeological conditions for underground disposal of wastewater, with the justification of the choice of an aquifer as an absorbing reservoir bed. For the analysis and assessment of the current control of the hydrodynamic parameters of the absorbing reservoir, the data of test, single and cluster pumping and injection in wells were used, taking as the calculation scheme of a pressure unlimited absorbing horizon. The studies to determine the compatibility of wastewater with formation waters of the horizon were carried out both by calculation methods, including physical and mathematical modeling, and experimentally. The analysis of the filtration parameters of the absorbing reservoir was performed based on the results of hydrodynamic studies.